Dynamic contrast-enhanced computed tomography perfusion parameters of canine suspected brain tumors at baseline and during radiotherapy might be different depending on tumor location but not associated with survival - Mortier, Jeremy R.; Maddox, Thomas W.; Blackwood, Laura; La Fontaine, Matthew D.; Busoni, Valeria (Frontiers in Veterinary Science, 2023)
Introduction: Treatment of brain tumors in dogs can be associated with significant morbidity and reliable prognostic factors are lacking. Dynamic contrast-enhanced computed tomography (DCECT) can be used to assess tumor perfusion. The objectives of this study were to assess perfusion parameters and change in size of suspected brain tumors before and during radiotherapy (RT) depending on their location and find a potential correlation with survival. Methods: seventeen client-owned dogs with suspected brain tumors were prospectively recruited. All dogs had a baseline DCECT to assess mass size, blood volume (BV), blood flow (BF) and transit time (TT). Twelve dogs had a repeat DCECT after 12 Gy of megavoltage RT. Survival times were calculated. Results: Intra-axial masses had lower BF (P= .005) and BV (P< .001) than extra-axial masses but not than pituitary masses. Pituitary masses had lower BF (P= .001) and BV (P= .004) than extra-axial masses. The volume of the mass was positively associated with TT (P= .001) but not with BF and BV. intra-axial masses showed a more marked decrease in size than extra-axial and pituitary masses during RT (P= .022 for length, P= .05 for height). Extra-axial masses showed a greater decrease in BF (P= .011) and BV (P= .012) during RT than pituitary masses and intra-axial masses. Heavier dogs had a shorter survival time (P = .011). Perfusion parameters were not correlated with survival. Conclusion: DCECT perfusion parameters and change in size of brain masses during RT might be different based on the location of the mass.